Green synthesis of metal oxide nanoparticles and their catalytic activity for the reduction of aldehydes. (February 2019) - Muthuvinothini, A.; Stella, S.
Graphical abstract: Highlights: Metal Oxide (MO) nanoparticles were synthesized using a green synthetic method and characterized. The catalytic property of the synthesized MO nanoparticles were examined. A green protocol for the reduction of aromatic aldehydes is demonstrated. Abstract: In the present work, a green synthesis of Metal Oxide nanoparticles was demonstrated using the freshly prepared aqueous extract of the immature fruit of Cocos nucifera and the MO nanoparticles were characterized by the analytical techniques such as UV–vis, FT-IR, XRD, SEM, TEM and EDAX. Characterization techniques confirmed that the biomolecules involved in the formation of nanoparticles and also they stabilized the nanoparticles. The synthesized MO nanoparticles were used as catalysts for the reduction of aromatic aldehydes. The reduction was done at mild reaction conditions using ammonium formate as a green hydrogen donor and the corresponding alcohols were obtained in 2–24 h with excellent yields. The reduction reaction was optimized using various solvents, loading of catalyst and at different temperatures.